Making Websites More Accessible For Blind People With Automatic HTML Code Transformations - Ferreira, Ana; Ribeiro, Márcio (Anais Estendidos do Congresso Brasileiro de Software: Teoria e Prática (CBSoft), 2023)
The Brazilian Inclusion Law (LBI) establishes mandatory accessibility rules on all websites. However, only 0.74% of the Brazilian websites meet the accessibility rules. Existing tools are capable of identifying accessibility problems (e.g., lack of images descriptions, lack of language information etc) when considering blind people that use screen readers to navigate on websites. Nevertheless, these tools do not provide transformations to remove the problems. To minimize this scenario, in this paper we introduce a preliminary catalog and a Visual Studio Code IDE plugin to make websites more accessible. The catalog presents some transformations on HTML code and the plugin implement them. We evaluate our catalog and plugin in a two-fold empirical study: with online evaluators, that are capable of scoring HTML code in terms of accessibility; and with eight blind people. The results show that the catalog and plugin can reduce the number of critical errors in terms of accessibility and that the majority of the blind participants was able to identify our improvements.